Ways of the Scientific World-Conception. Rudolf Carnap and Otto Neurath - Damböck, Christian,; Friedl, Johannes,; Höfer, Ulf, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2024)
Rudolf Carnap (1891-1970) and Otto Neurath (1882-1945) had a decisive influence on the development of the scientific world view of logical empiricism. Their relationship was marked by mutual intellectual stimulation, close collaboration, and per